Newnes industrial control wiring guide - Mercer, Bob. (Oxford ; Boston : Newnes, 2001)
This Newnes manual provides a practical introduction to the standard methods and techniques of assembly and wiring of electrical and electromechanical control panels and equipment. Electricians and technicians will find this a useful reference during training and a helpful memory aid at work. This is a highly illustrated guide, designed for ready use. The contents are presented in pictures and checklists. Each page has a series of 'how-to' instructions and illustrations. In this way the subject is covered in a manner which is easy to follow. Each step adds up to a comprehensive course in control panel wiring. This new edition includes extra underlying theory to help the technician plus application notes and limitations of use. Simple programmable logic controllers (PLCs) are covered, as well as new information about EMC/EMI regulations and their impact. A highly illustrated step-by-step approach. Practical and easy to follow. A comprehensive course in control panel wiring.
Safety -- Drawings -- Wire types and preparation -- Soldering and termination -- Cable forming -- Hardware -- Components (active) -- Components (passive) -- Switches and lamps -- Earthing and screening -- Index.
Includes index.
Keywords: Electric wiring -- Handbooks, manuals, etc; Factories -- Electric equipment -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc